Daughters Birth Daughters and Virgins Birth Sons. The Virgin Birth in Aphids, Bees and... Humans? - Kłoskowicz, Małgorzata; Świątek, Piotr (No Limits, 2023)
How is it possible that a virgin queen, who was unable to fly out of the hive for her first and only mating flight, laid unfertilised eggs? What’s more: viable males, i.e. drones, hatched from the eggs. This was the question that Rev. Jan Dzierżon, a beekeeper living at the turn of the 20th century, an enthusiast and inventor of the prototype of the modern hive, had to ask himself when he first observed virgin birth in bees. We now know that natural parthenogenesis (virgin birth) is observed not only in insects and many other invertebrates but also in fish, amphibians, reptiles, and birds. It does not occur in mammals, although, as experiments have shown, it can be artificially induced in mice, but not yet in humans.